New results of frequency weighted balanced truncation technique on Schur Decomposition - Sahlan, Shafishuhaza (IEEE, 2011)
In this paper, we present some new results on frequency weighted balanced technique based on partial fraction expansion idea in discrete-time system. The reduced order models obtained are guaranteed to be stable even for double sided weightings by direct truncation. A simple and easily computable a priori error bound is derived. Numerical example shows the effectiveness of the proposed method.